Religious Activities and Empowerment : Sustainable Livelihood Framework Approach In Enhancing The Desa Luworo Potencies - Achmad Room Fitrianto (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
The marginality and governmental alignments are the two main issues in community development. The role of Tengkulak Rentenir, and Pengijon are significant in Luworo Village. Not only as a financial provider, they also play as connector among the peasant farmer and market. As a result the farmer receipts their selling agricultural productions below market prices. In order to support and giving additional value to their agricultural products an assistance program involving a female Islamic study group of Masjid Al-Hidayah conducted. The assistance activities conducted through SLF approach. The five phases of SLF are: identifying vulnerability; mapping the livelihood assets owned by the community; observing transforming structures and processes; and identifying livelihood strategies and formulating livelihood outcomes.